2011
DOI: 10.1093/schbul/sbr006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment With Aripiprazole Prevents Development of Dopamine Supersensitivity and Potentially Supersensitivity Psychosis

Abstract: Background: Long-term treatment of schizophrenia with antipsychotics is crucial for relapse prevention, but a prolonged blockade of D2 dopamine receptors may lead to the development of supersensitivity psychosis. We investigated the chronic effects of aripiprazole (ARI) on dopamine sensitivity. Methods: We administered ARI (1.5 mg/kg/d), haloperidol (HAL; 0.75 mg/kg/d), or vehicle (VEH) via minipump for 14 days to drug-naive rats or to rats pretreated with HAL (0.75 mg/kg/d) or VEH via minipump for 14 days. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 28 publications
3
82
0
Order By: Relevance
“…The increase is similar to that induced by nigrostriatal lesions [7]. In animal models, increased D 2 density is associated with behavioral supersensitivity to dopamine stimulation manifested by TD-like symptoms [42,43], increased psychomotor activity in response to the dopamine agonists amphetamine and apomorphine [44,45,46], decreased efficacy in models of antipsychotic-like effects [9,10], and increased pursuit of reward cues in response to amphetamine [11,12,13]. Many of the older animal studies showing that chronic antipsychotic treatment produces dopamine D 2 receptor upregulation have used very high doses of antipsychotic/D 2 receptor occupancy.…”
Section: Pharmacological Mechanisms By Which Antipsychotics Potentialmentioning
confidence: 89%
See 3 more Smart Citations
“…The increase is similar to that induced by nigrostriatal lesions [7]. In animal models, increased D 2 density is associated with behavioral supersensitivity to dopamine stimulation manifested by TD-like symptoms [42,43], increased psychomotor activity in response to the dopamine agonists amphetamine and apomorphine [44,45,46], decreased efficacy in models of antipsychotic-like effects [9,10], and increased pursuit of reward cues in response to amphetamine [11,12,13]. Many of the older animal studies showing that chronic antipsychotic treatment produces dopamine D 2 receptor upregulation have used very high doses of antipsychotic/D 2 receptor occupancy.…”
Section: Pharmacological Mechanisms By Which Antipsychotics Potentialmentioning
confidence: 89%
“…Long-term administration of antipsychotics, through D 2 receptor blockade, increases D 2 receptor density in the striatum [42,43,44,45], either through an increase in D 2 receptor synthesis, a decrease in D 2 receptor degradation, or both. The increase is similar to that induced by nigrostriatal lesions [7].…”
Section: Pharmacological Mechanisms By Which Antipsychotics Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it has been reported that the density of D2-R in the striatum is not increased by administration of ARI in animal studies in contrast to administration of full antagonists [14]. Further, the density of D2-R that had once been increased by haloperidol administration is decreased to the level of the control group by administration of ARI [39].…”
Section: Discussionmentioning
confidence: 90%